∫1/(1+e^x)^2dx
来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/01 09:56:20
∫1/(1+e^x)^2dx∫1/(1+e^x)^2dx∫1/(1+e^x)^2dx令a=1+e^xx=ln(a-1)dx=da/(a-1)原式=∫da/a²(a-1)1/a²(a
∫1/(1+e^x)^2dx
∫1/(1+e^x)^2dx
∫1/(1+e^x)^2dx
令a=1+e^x
x=ln(a-1)
dx=da/(a-1)
原式=∫da/a²(a-1)
1/a²(a-1)=m/a+n/a²+p/(a-1)
则p=1,m=n=-1
原式=∫[-1/a-1/a²+1/(a-1)]da
=-lna+1/a+ln(a-1)+C
=-ln(1+e^x)+1/(1+e^x)+x+C
先令y=1+e^x => x=ln(y-1),dx=dy/(y-1)
利用上式可得:
∫1/(1+e^x)^2dx
=∫1/y^2*dy/(y-1)
=∫dy/[y^2(y-1)]
拆分1/[y^2(y-1)]成a/y^2+b/y+c/(y-1)
a(y-1)+by(y-1)+cy^2=1 => a=-1,b=-1,c=1
则1/[y^2(y...
全部展开
先令y=1+e^x => x=ln(y-1),dx=dy/(y-1)
利用上式可得:
∫1/(1+e^x)^2dx
=∫1/y^2*dy/(y-1)
=∫dy/[y^2(y-1)]
拆分1/[y^2(y-1)]成a/y^2+b/y+c/(y-1)
a(y-1)+by(y-1)+cy^2=1 => a=-1,b=-1,c=1
则1/[y^2(y-1)]=-1/y^2-1/y+1/(y-1)
∫dy/[y^2(y-1)]
=∫[-1/y^2-1/y+1/(y-1)]dy
=1/y-ln|y|+ln|y-1|+C
=1/(1+e^x)-ln(1+e^x)+x+C
收起
∫[dx/(e^x(1+e^2x)]dx
∫ e^x-e^(-x)dx=e^x+e^(-x)|=e+1/e-2
∫1/(e^x+e^(-x))dx,
∫1/(1+e^x)^2dx
∫dx/√[1-e^(-2x)]
求不定积分∫(e^(2x)-1) / e^x dx
∫ e^x/[e^(-2x)+1] dx
∫e^2x/√e^x+1 dx
∫(e^2x)-1/(e^x)dx求不定积分
∫e^2x/√e^x+1 dx
∫e^x(1+e^x)^2dx
求不定积分:∫(e^3x+e^x)dx/(e^4x-e^2x +1)
∫1/x^4 dx 和∫1/e^x dx ∫1/e^2x dx ∫1/e^2 dx 不定积分解法
∫(e,e^2)lnx/(x-1)^2dx
求∫(e,e^2) lnx/(x-1)^2 dx
求不定积分∫[(e^(3x)-1)/(e^(x)-1)]dx怎样得出∫[(e^(x)-1)(e^(2x)+e^(x)+1)/(e^(x)-1)]dx
求不定积分∫(e^3x-e^x)/(e^4x+3e^2+1)dx
∫e^(x^2)x(1+x^2)dx